2018
DOI: 10.1016/j.respol.2018.04.022
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of regional subsidies for collaborative and individual R&D in small and medium-sized enterprises

Abstract: We analyse whether public subsidies supporting collaborative research and development (R&D) projects in small and medium-sized enterprises (SMEs) are able to encourage persistent R&D investment and interorganisational networking more than subsidies supporting individual R&D projects. Adopting a counterfactual approach to policy evaluation, we compare subsidies for collaborative R&D and for individual R&D implemented in the same Italian region in the same period. Our findings suggest that, once public support i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 74 publications
(76 reference statements)
2
20
0
Order By: Relevance
“…We therefore confirm the results obtained for other collaboration-based policies (regional support to R&D collaboration) in various countries regarding the ability of public incentives to generate collaboration additionality (Afcha Chavez, 2011;Nishimura and Okamuro, 2011;Caloffi et al, 2018Caloffi et al, , 2011. We add to these previous results in providing specific insights regarding the lack of local impact (H2) of cluster policies, at least in France.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We therefore confirm the results obtained for other collaboration-based policies (regional support to R&D collaboration) in various countries regarding the ability of public incentives to generate collaboration additionality (Afcha Chavez, 2011;Nishimura and Okamuro, 2011;Caloffi et al, 2018Caloffi et al, , 2011. We add to these previous results in providing specific insights regarding the lack of local impact (H2) of cluster policies, at least in France.…”
Section: Resultssupporting
confidence: 86%
“…We rely on the standardised mean difference (SMD) to assess the balance in baseline characteristics between treated and control groups (Austin and Stuart, 2015;Caloffi et al, 2018). While there is no consensus as to what value of a standardised mean difference can be considered as an indication of imbalance, several authors have suggested that a standardised mean difference in excess of 0.1 may be indicative of meaningful imbalance in a covariate between treated and control subjects (e.g.…”
Section: Econometric Approachmentioning
confidence: 99%
“…In order to formulate some hypotheses, we refer to the theoretical and empirical findings of the literature on R&D collaborations, and adapt the main ideas to the specific object of our analysis. We will draw from the following fields of literature: first, the studies that have considered the effect of alternative configurations of large-scale policy-elicited R&D consortia on firms' or projects' outcomes (Branstetter & Sakakibara, 2002;Bizan, 2003;Sakakibara & Branstetter, 2003;Schwartz et al, 2012;Spanos et al, 2015); second, the studies that have analysed (mostly pairwise and/or mostly spontaneous) R&D collaborations involving SMEs (Belderbos, Carree, & Lokshin, 2004;Okamuro, 2007;Marzucchi et al, 2016;Caloffi, Mariani, Rossi, & Russo, 2018).…”
Section: Are All Partnerships Good For Smes?mentioning
confidence: 99%
“…However, no matter which level of openness and what type of innovation, they are closely related to innovation capability. Firms should try their best to improve their innovation capability [66].…”
Section: Management Implicationsmentioning
confidence: 99%